Оқушылардың танымдық іс-әрекеті арқылы оқу мәдениетін басқарудағы мұғалім ұстанымдары - Омарова, Г.Ә.; Наханова, Б.; Абдришева, С.А. (My University, 2013)
The methods and the positions of the teachers who manage the administration of the reading culture through the cognitive activities of the pupils are described in this article .